2015
DOI: 10.9775/kvfd.2014.11664
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’nin Güneydoğu Bölgesi’nde Üretilen Mısır Silajı ve Çiğ Sütlerde Listeria Türlerinin Varlığı

Abstract: The objective of this study was to investigate the presence of Listeria species in the corn silage and raw milk samples. A total of 140 raw milk samples obtained from cows, sheeps and goats fed with silage and 90 corn silage samples collected from 10 dairy farms in SouthEastern Region of Turkey were analyzed for Listeria spp. In the result, L. monocytogenes and L. innocua were isolated from 2 (2.2%) and 5 (5.5%) silage samples and from 3 (2.1%) and 5 (3.5%) raw milk samples, respectively. The results indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…Our findings were noticed that the frequency of isolation of L. monocytogenes was much lower. This observation also agrees with that of VardarÜnlü et al, (1998), Sağun et al, (2001), Aygun and Pehlivanlar, (2006), Taşçı et al, (2010), Abay et al, (2012), and Durmaz et al, (2015), who found 4% in Sivas, 1.2% in Van, 0% in Antakya, 2.4% in Burdur, 0% in Kayseri, and 2.2% in Şanlıurfa and Adıyaman, respectively. In other countries, as opposed to our study, the reported isolation rates of L. monocytogenes from raw milk samples were 16.7% in Brazil (Silva et al, 2003), 6.5% in United States (van Kessel et al, 2004), 4% in Iran (Jami et al, 2010), 22% in Ethiopia (Gebretsadik et al, 2011), 6.3% in Ireland (Fox et al, 2011), 41.6% in Syria (Al-Mariri et al, 2013), 21.7% in Malaysia (Jamali et al, 2013), and 16.6% in India (Nayak et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings were noticed that the frequency of isolation of L. monocytogenes was much lower. This observation also agrees with that of VardarÜnlü et al, (1998), Sağun et al, (2001), Aygun and Pehlivanlar, (2006), Taşçı et al, (2010), Abay et al, (2012), and Durmaz et al, (2015), who found 4% in Sivas, 1.2% in Van, 0% in Antakya, 2.4% in Burdur, 0% in Kayseri, and 2.2% in Şanlıurfa and Adıyaman, respectively. In other countries, as opposed to our study, the reported isolation rates of L. monocytogenes from raw milk samples were 16.7% in Brazil (Silva et al, 2003), 6.5% in United States (van Kessel et al, 2004), 4% in Iran (Jami et al, 2010), 22% in Ethiopia (Gebretsadik et al, 2011), 6.3% in Ireland (Fox et al, 2011), 41.6% in Syria (Al-Mariri et al, 2013), 21.7% in Malaysia (Jamali et al, 2013), and 16.6% in India (Nayak et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…In this respect, according to Muck (2010), substantial concentrations of enterobacteria result in a reduction of dietary intake. To minimize the action of these deteriorating microorganisms, it is necessary to use additives that improve the fermentation profile of the silage (Durmaz et al, 2015). In the specific case of our study, the cactus silage without inoculant also exhibited an adequate fermentation pattern, which explains the lack of an effect on the animals.…”
Section: Tablementioning
confidence: 79%
“…The main factors affecting LA production level and speed are epiphytic lactic acid bacteria (LAB) on forage and chemical composition of crop material [1] . Silage quality is largely depends on competition between LAB and other microorganism groups [2] . Enough LA production decreases proteolysis and even can completely stop when pH level comes to below a level of 4 [3] .…”
Section: Intoductionmentioning
confidence: 99%